Ice wedge evidence in the Mesa Range (northern Victoria Land, Antarctica) - RAFFI, Rossana; B. STENNI; O. FLORA; S. POLESELLO; M. CAMUSSO (Terra Antartica Publication, 2003)
The morphologic features of the ice wedge were defined, and the crystal texture and fabric of the ice crystals were determined. A co-isotopic study measured both oxygen (d18O) and hydrogen (dD) isotope compositions. Tritium activity was measured, and major cations and anions were determined in the same samples. The study aimed to define the origin of the ice forming the wedge and establish whether the wedge growth processes are still active under the present climatic conditions.